THE IMPACT OF THE PROBLEM BASED TUTORIAL MODEL IMPLEMENTATION ON STUDENTS’ ABILITY IN DESIGNING CLASSROOM ACTION RESEARCH AND WRITING A SCIENTIFIC REPORT - Tri Dyah Prastiti; Sudilah Sudilah (Universitas Ahmad Dahlan, 2016)
This paper is written based on the research done to the 6th semester students of PGSD (Elementary School Teacher Training Program), Faculty of Teacher Training and Education (FKIP), Universitas Terbuka. The study aimed to describe the impact of the implementation of Problem Based Tutorial Model (PBTM) in Classroom Action Research (CAR) tutorial activities on the students’ ability in designing CAR and writing a scientific report. The model is designed to help the students to implement the concept of CAR in their own teaching, and to make the report of the study in a well-written scientific writing. The model consists of Tutorial Activity Unit, Tutorial Design Activity, Student Worksheets and Evaluation Design. The results of study showed that after the implementation of the model the students were able to design a class room action research well. Each part of the report was written appropriately. Part I consists of introduction, part II (review of the related literature), and part III (results and discussion). The first study was done with students of PGSD at Magelang learning cluster. The average scores of the reports was 87, whereas those done in Temanggung was 87,43. This result showed the increase of the students’ ability in writing a scientific report. Furthermore, the impact of the implementation of the model in Pokjar Temanggung showed higher scores than that of the previous implementation (in Pokjar Magelang) with the level of confidence 99%.